Christmas oranges [videorecording (DVD)] - Herrmann, Edward, 1943-2014; Stafford, Nancy, 1954-; Johnson, Bailee; Bethers, Linda (Bridgestone, 2012)
In a town not so far away and a time not so long ago, baby Rose was left on the porch of Greenwoods Orphanage, where Mrs. Hartley (Nancy Stafford) and the children under her tender care become her family. But when tragedy strikes, Rose (Bailee Johnson) loses the only home she has ever known and she is abruptly shipped to Irongates--a place that seems as cold and cruel as her previous home was kind. The strict headmaster, Mr. Crampton (Edward Herrmann), immediately seems to dislike Rose--and makes sure she and the other children are punished for any minor infraction of his rules. Then on Christmas morning, a miracle happens.